Randomized Clinical Investigation of Titanium Implants with and without Platform Switching: Six Months' Radiographic and Clinical Outcome - Roberto Rossi; Diego Capri; Emanuele Risciotti; Paul Zeman (MDPI AG, 2015)
The aim of this study was to obtain a randomized, clinical and radiological comparison of implants with and without platform switching (PFS). The two compared titanium implant types differed only in the microgap position: test (PFS) or control (StE, no PFS). All implants were inserted in posterior regions and followed up for six months after abutment connection (AC). Twenty one patients with 21 PFS and 18 StE implants completed the six-month evaluation. No implant failed. One complication (exposed cap screw) was reported at AC. No statistically significant difference was observed between the marginal bone level of PFS and StE implants. Their bone level stabilized approximately 1 mm below the microgap. Based on the outcome of this short-term study with a limited number of patients, it seems unlikely that the optimal clinical and radiological outcome obtained with the tested standard implant (no PFS) can be improved by introducing an inward microgap shift (PFS).